RAPD FINGERPRINTING OF THREE SPECIES OF GROUPER (Epinephelus spp.) FROM MAKASSAR STRAIT, SOUTH SULAWESI, INDONESIA - Andi Parenrengi (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2006)
Grouper belonging to the epinepheline serranid family has promising aquaculture potential for food and ornamental fish production. Random amplified polymorphic DNA (RAPD) technique was employed in this study to determine the genetic variability and species differentiation of groupers from genus Epinephelus (E. areolatus, E. merra, and E. suillus). Groupers (N=52) were collected from Makassar Strait, South Sulawesi, Indonesia. Of 34-screened RAPD primers, ten primers (OPA-02, OPA-06, OPA-08, OPA-10, OPA-15, OPA-16, OPA-17, OPA-18, OPA-19, and CA-05) were selected to generate the RAPD fingerprinting of groupers. Results indicated that the ten primers revealed different RAPD profile among three species. Similarity index obtained by pairwise comparison was 0.62 ± 0.07 for E. areolatus, 0.58 ± 0.11 for E. merra and 0.80 ± 0.11 for E. suillus. Polymorphism and genotype number detected were 51.3% ± 8.7% and 3.8 ± 0.6 in E. areolatus; 56.8% ± 14.6% and 4.1 ± 1.1 in E. merra; and 60.2% ± 11.8% and 3.8 ± 0.9 in E. suillus, respectively. Genetic distance level of individuals ranges from 0.19—0.42, 0.14—0.50, and 0.02—0.30 for E. areolatus, E. merra, and E. suillus, respectively. The genetic distance between E. merra and E. areolatus (D=0.52) was closer compared with E. merra and E. suillus (D=0.67). A total of 33 RAPD markers differentiating the three species of groupers were detected. The study presents the RAPD technique as the useful genetic marker for assessment of genetic diversity and species differentiation in groupers.